1989
DOI: 10.1364/ol.14.000015
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of three-photon ionization of atomic hydrogen and deuterium at 243 nm

Abstract: Two-photon-resonant, three-photon ionization of atomic hydrogen and deuterium is performed at 243 nm, and the ions are detected by time-of-flight mass spectrometry. The power dependence of the 1S-2S two-photon excitation and one-photon ionization of 2S hydrogen and deuterium are determined. The ionization step saturates at 4 x 10(6) W/cm(2). The two-photon step-power dependence varies with laser linewidth, with saturation occurring between 1 x 10(7) and 3 x 10(7) W/cm(2). The extraction electric field in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Since we also used some deuterated species to determine the origin of the photolysis fragment, it should be mentioned that the ͑2+1͒ REMPI process for D atoms occurs at 243.00 nm, 31 well outside the 0.04 nm bandwidth of the ionizing laser. Besides, the heavier D fragments would arrive to the detector approximately 2 s later than the lighter H fragments, i.e., in the TOF-spectra region where we see no signal.…”
mentioning
confidence: 99%
“…Since we also used some deuterated species to determine the origin of the photolysis fragment, it should be mentioned that the ͑2+1͒ REMPI process for D atoms occurs at 243.00 nm, 31 well outside the 0.04 nm bandwidth of the ionizing laser. Besides, the heavier D fragments would arrive to the detector approximately 2 s later than the lighter H fragments, i.e., in the TOF-spectra region where we see no signal.…”
mentioning
confidence: 99%
“…Thermal dissociation of some CO molecules which collided with the wire filament and grid produced ground state oxygen atoms. Ground electronic state hydrogen and deuterium ;ztoms have been produced from beams of molecular hydrogen and deuterium using this technique as recently described by Downey and Hozack (1989). Laser power dependence measurements for the detection of these atoms gave a value n = 2.73 ±0.28, and computer simulation of the experimental excitation spectra gave a distribution with a temperature of 340 ±40 K. We observed that essentially no 0* signal was generated by the filament from the thermal dissociation of CO when the applied current was very low.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the secondary-ion energy window is 180 eV, which corresponds to a 150 Mm wide region above the sample in this extraction geometry. Laser beam edge effects are not as important as in gaseous-sample photoionization power-dependence ex-periments where samples are not confined and extraction volumes are large (8).…”
Section: Resultsmentioning
confidence: 99%